Toward Systems Biomarkers of Response to Immune Checkpoint Blockers - Lapuente-Santana, Óscar; Eduati, Federica (Frontiers in Oncology, 2020)
Immunotherapy with checkpoint blockers (ICBs), aimed at unleashing the immune response towards tumor cells, has shown a great improvement in overall patient survival compared to standard therapy, but only on a subset of the patients. In recent years, huge efforts have been invested in the identification of factors that affect ICBs efficacy, providing a number of potential predictive biomarkers such as PD-L1 expression, neoantigen load, or different types of genetic alterations. These studies have significantly improved our understanding of some mechanisms playing an important role in the tumor microenvironment (TME), however we still struggle to effectively predict the large heterogeneity of patients’ response to ICBs. In this Mini Review, we focus on how the increasingly available multi-omics data allow taking into account the complexity of the TME, enabling a holistic approach towards the definition of new predictive biomarkers. In particular, we review how different types of immune cells influence the efficacy of ICBs, not only in terms of their quantification, but also considering their localization and functional state. Additionally, we describe how multi-omics data can be used to study intra-cellular networks, which play an important role in shaping the immune response and are responsible for resistance to immunotherapy. Finally, we highlight the importance of combining multi-omics data and computational models in defining new biomarkers that can take into account the dynamic nature of the complex interactions taking place in the TME.